Physiological and transcriptional analyses of Arabidopsis primary root growth in response to phosphate starvation under light and dark conditions - Zhen Wang; Mingzhe Xia; Rui Ma; Zai Zheng (Frontiers in Plant Science)
Plants cope with Pi deficiency by triggering an array of adaptive responses, including the remodeling of root system architecture (RSA). Arabidopsis thaliana grown on a Pi-deficient (-Pi) medium in transparent Petri dishes exhibits an inhibition of primary root (PR) growth. Previous work has shown that direct illumination on roots by blue light is both required and sufficient for the Pi deficiency-induced inhibition of PR growth. However, whether light illumination on shoots of seedlings contributes to the inhibition of PR growth under -Pi condition and whether light signaling pathway is involved in this process remain largely unknown. In addition to Pi deficiency-induced inhibition of PR growth, how light affects the transcriptomic changes under -Pi also remains elusive. Here, we found that the inhibition of PR growth under -Pi condition is determined by light illumination on roots instead of shoots. Further experiments revealed that blue light receptors CRY1/CRY2 and key regulator in blue light signaling pathway HY5 play minor roles in this process. Finally, we evaluated the light effects on the transcriptomic changes during the inhibition of PR growth under -Pi condition. We found that light promotes the expression of many genes involved in stress and phytohormones-related processes and has both upregulated and downregulated effects on the expression of typical phosphate starvation-induced (PSI) genes. Taken together, our work further demonstrates our previous hypothesis that the inhibition of PR growth under -Pi condition is caused by blue light-triggered chemical reactions, rather than blue light signaling pathways. Apart from the inhibition of PR growth under -Pi, light exposure also results in substantial alterations of transcriptome under -Pi condition, encouraging us to carefully evaluate the phenotype under illuminated, transparent Petri dishes.